2007
DOI: 10.1007/s00535-006-1965-0
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of hepatopulmonary syndrome with improved liver function following long-term oxygen therapy

Abstract: Hepatopulmonary syndrome (HPS) is a complication of liver disease that is characterized by hypoxemia and intrapulmonary vascular dilatations. The only established therapy for this disorder is liver transplantation. Here, we report two patients (a 63-year-old woman and a 72-year-old man) with HPS associated with hepatitis C virus-related cirrhosis. We gave the patients low-dose oxygen supplementation to improve their respiratory symptoms. Surprisingly, their liver function improved from Child Pugh class C to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
5
0
6
Order By: Relevance
“…Fukushima et al 31 have shown that treatment for 1 year had a beneficial effect on liver function in two patients (their Child-Pugh score markedly improved).…”
Section: Oxygen Therapymentioning
confidence: 98%
“…Fukushima et al 31 have shown that treatment for 1 year had a beneficial effect on liver function in two patients (their Child-Pugh score markedly improved).…”
Section: Oxygen Therapymentioning
confidence: 98%
“…Se ha determinado que la hipoxemia es un predictor independiente de la sobrevivencia del paciente portador de SHP y además puede contr deterioro de la función hepática [45].…”
Section: Oxígeno Suplementariounclassified
“…En un estudio se les administró oxígeno suplementario en bajas dosis a pacientes con SHP para mejorar los síntomas respiratorios, sorprendentemente la función hepática mejoró de Child Pugh clase C a clas A, y la ascitis desapareció después de un año de administrar oxígeno suplementario a estos pacientes [45]. Se manifiesta que la terapia con oxígeno a largo plazo ha contribuido en la mejoría de la función hepática en los casos estudiados [45].…”
Section: Oxígeno Suplementariounclassified
See 1 more Smart Citation
“…Не-смотря на то что кислородотерапия у этих пациентов не в состоянии полностью устранить гипоксемию, в литературе описывается выраженный клиниче-ский эффект у части больных [19]. В настоящее время длительная кислородотерапия рекомендована всем пациентам с гепатопульмональным синдромом, не-смотря на то что нет доказательств улучшения выжи-ваемости больных на фоне данного метода лечения.…”
unclassified